Some Early Eighteenth-Century Roman Catholic Recusants - Huelin, Gordon (The journal of ecclesiastical history, 1956)
Among the archives belonging to the diocese of London and housed in two muniment rooms in St. Paul's Cathedral, is a bundle of papers labelled ‘Certificates as to Papists, 1706’. Curiosity having tempted me to undo and examine its contents, I now give a survey of the documents therein contained, believing that this may prove to be of value in two respects: first, as throwing new light upon members of a proscribed religion at a time which, so far as can be ascertained from books and records in libraries, Catholic and non-Catholic alike, is very poorly documented; secondly, as giving yet another insight into the character and outlook of a section of the Anglican clergy at the beginning of the eighteenth century.